Técnica para dedução do modelo algébrico PTT, aplicações e análises numéricas em escoamentos bidimensionais - Dolci, Daiane Iglesia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work presents the theoretical development of the algebraic model PTT (Phan- Thien-Tanner) and its application to the simulation of viscoelastic flows. The implementation and numerical solutions are obtained in the simulation framework FREEFLOW -2D. The numerical methodology used to solve the algebraic PTT model is based on the finite difference method with discretization on a staggered grid. The fluid is modeled using the MAC (Marker-and-Cell) technique which allows for visualization and location the free surface of the fluid. The temporal derivative of the momentum equation and of the algebraic PTT model are approximated by the implicit and explicit Euler’s methods. The convective term are approximate by the ‘upwind’ high order method CUBISTA (Convergent and Universally Bounded Interpolation Scheme for the Treament of Advection) and spatial derivatives by central differences. The numerical methodology verification is performed in a simulation of a confined flow fully developed in a channel, comparing the numerical solution with the analytical solution which is obtained by the algebraic PTT model. Still considering a viscoelastic flow in the channel, is compared the computational effort of the simulations using the algebraic model and differential model. Another problem proposed to verify the performance of the algebraic PTT model is the planar contraction 4:1. This geometry also they expose themselves comparisons of the computational effort of the simulations given by the algebraic model and the differential model. As application of free surface flows, the algebraic model is tested in simulations of a viscoelastic drop in a rigid plate (Impacting Drop). The numerical results are compared with the expected results obtained by the differential PTT model.

Neste trabalho é apresentado o desenvolvimento teórico do modelo algébrico PTT (Phan-Thien-Tanner) e aplicação na simulação de escoamentos viscoelásticos. A implementação e obtenção das soluções numéricas são realizadas no ambiente de simulação FREEFLOW-2D. A metodologia numérica a ser empregada para resolver o modelo algébrico PTT é baseada no método de diferenças finitas, com discretização em uma malha deslocada. O fluido é modelado utilizando a técnica MAC (Marker-and-Cell ) o que permite visualizar e localizar a superfície livre do fluido. As derivadas temporais da equação de quantidade de movimento e do modelo algébrico PTT são aproximadas pelos métodos de Euler implícito e Euler explícito, respectivamente. Os termos convectivos são aproximados pelo método ‘upwind’ de alta ordem CUBISTA (Convergent and Universally Bounded Interpolation Scheme for the Treament of Advection) e as derivadas espaciais por diferenças centrais. A verificação da metodologia numérica é feita na simulação de um escoamento confinado totalmente desenvolvido em um canal, comparando os resultados da solução numérica com a solução analítica que, neste trabalho, é obtida a partir do modelo algébrico PTT. Ainda considerando um escoamento viscoelástico no canal, é comparado o esforço computacional das simulações que utilizam o modelo algébrico e o modelo diferencial. Outro problema proposto para verificar o desempenho do modelo algébrico PTT é a contração abrupta 4:1, nessa geometria também expõem-se comparações do esforço computacional das simulações dadas pelo modelo algébrico e pelo modelo diferencial. Como aplicação em escoamentos com superfície livre, o modelo algébrico é testado em simulações de uma gota viscoelástica em uma placa rígida (Impacting Drop). Os resultados numéricos são comparados com os previstos pelo modelo diferencial PTT.
Keywords: Computação - Matematica; Algebra (Computadores); Álgebra tensorial; Fluidos newtonianos; Fluidos não-newtonianos; Modelos matematicos; Computer science - Mathematics